Assessing the stock recovery of Coilia nasus in the Yangtze River-Poyang Lake waterway and adjacent waters, using the length-based Bayesian biomass method - Yulan Luo; Qun Xu; Sheng Wang; Zhengli Luo; Chiping Kong; Legen Peng; Bao Zhang; Baolong Bao; Lekang Li; Xiaoling Gong (Frontiers in Marine Science, 2025)
The comprehensive ten-year fishing ban implemented in the Yangtze River on January 1, 2021, represents a critical ecological conservation measure and national strategic priority in China. Assessment of the ban’s effectiveness is essential to guide future long-term conservation efforts. This study systematically analyzed changes in the stock structure and biomass dynamics of Coilia nasus in the Yangtze River-Poyang Lake waterway and adjacent waters from 2019 to 2024 using the Length-Based Bayesian Biomass (LBB) method. Results showed a notable improvement in age structure, with the proportion of four-year-old individuals increasing from 3.2% in 2020 to 17.2% in 2024, effectively reversing the previous trend toward younger, smaller fish. The average body length and weight increased significantly, from 271.20 ± 38.44 mm, 68.52 ± 33.26 g in 2019 to 305.53 ± 37.99 mm, 88.02 ± 32.01 g in 2024 ( P < 0.05). The dominant size classes shifted step by step, from 250 – 260 mm, 50 – 60 g in 2019 to 330 – 340 mm, 120 – 130 g in 2024. According to the LBB model, the relative biomass ( B/B 0 ) increased from 0.17 to 0.68, and biomass relative to the maximum sustainable yield ( B/Bmsy ) rose from 0.48 to 1.9, demonstrating a transition in the stock status from “outside of safe biological limits” to “healthy” from 2019 to 2024. These trends, along with increases in the Lmean/Lopt , Lc/Lcopt ratios and other indexes, highlight improvements in size structure and a greater presence of larger individuals. In addition, the fishing mortality to natural mortality ratio ( F/M ) markedly declined from 2.6 in 2019 to 0.37 in 2024, underscoring the substantial alleviation of fishing pressure under the ban. To further validate these findings, SPR was estimated using the LBSPR model, increasing from 0.19 to 0.42 and suggesting improved reproductive sustainability. These findings provide strong evidence that the fishing ban has played a critical role in the stock recovery of C. nasus and mitigating the effects of overfishing.